Integrated reports and board's diversity: An international perspective - Lopes, A.I.; Braz, M.J. (Conceptual and theoretical approaches to corporate social responsibility, entrepreneurial orientation, and financial performance, 2020)
Organizations currently must report to a broader audience, capturing the attention of several categories of stakeholders, who want to know why, where, and how companies create and add value, and how they deal with responsibility and sustainability issues, contributing to the emerging of integrated reporting (IR). IR is as an innovation in promoting a holistic and integrated vision of the business, where the Board of Directors must play an important role. This chapter covers diversity of directors seated on the board of integrated reporters, comparing two groups: those who are IR references and those that are IR regular reporters. The results show that organizations with larger boards, higher proportions of non-executive directors, and a higher proportion of women on the board have an higher probability of preparing IR reference reports, while the duality role of CEO inverts the probability, and no relationship is found with board experience.